Development of a one-dimensional detector for diffraction experiments at the synchrotron radiation beam - Aulchenko, V. M.; Glushak, A. A.; Zhulanov, V. V.; Titov, V. M.; Shekhtman, L. I. (Journal of surface investigation: X-ray, synchrotron and neutron techniques)
The work describes a one-dimensional detector for diffraction experiments at a synchrotron radiation beam. The detector is being developed at the Budker Institute of Nuclear Physics, Siberian Branch, Russian Academy of Sciences. Until recently the institute was developing gas one-coordinate detectors, in particular a one-coordinate detector with calculated channels (OD-3M), based on the technology of multiwire proportional chambers. To provide a spatial resolution better than 100 microns at a photon energy in a wide energy range (3–30 keV), it is necessary to use solid-state microstrip or matrix sensors in combination with specialized integrated registration circuits. The developed SOCOD detector, using a microstrip sensor based on gallium arsenide as a registration element, operates in the mode of the direct counting of photons with an energy of more than 3–4 keV and a speed of up to 1 MHz/channel. The work gives a general description of the current version of the detector, a block diagram of the registration channel, the software allowing users to control the operation of the detector and display the results obtained, and the developed algorithm for leveling the trigger thresholds in the channels. The results of electronic tests, the work of the alignment algorithm and their discussion are presented.